CT-guided paravertebral injection of doxorubicin for treatment of postherpetic neuralgia: a database-based retrospective stratified study - Lu, Fan; Zhong, JiWei; Liu, Hui; Xiao, Hong (Frontiers in Neurology, 2023)
Objective This study explored the impact of different doeses of doxorubicin in CT-guided transvertebral foraminal injections for postherpetic neuralgia (PHN) treatment and the impact of 0.5% doxorubicin treatment on patients with different disease courses and lesion locations. Methods This retrospective study included 291 patients with PHN who received CT-guided doxorubicin injection at West China Hospital between April 2014 and February 2020. Results A total of 228 patients received 0.5% doxorubicin treatment and 63 received 0.33% doxorubicin. Both groups showed significantly improvement in visual analogue scale (VAS) and Brief Pain Inventory (BPI) scores. The 0.5% doxorubicin group demonstrated significant lower VAS scores at 6 and 12 months after surgery (all p < 0.001) and a significant lower score on the BPI at 6 and 12 months than the 0.33% doxorubicin group (all p < 0.05). Stratified analysis of 0.5% doxorubicin demonstrated a significant reduction in VAS score at 1 week, 3 months, 6 months, and 12 months after treatment compared to baseline (all p < 0.05) and significant improvements in BPI score after treatment compared to baseline (p < 0.05). The VAS score of the chest group was significant higher than facial, neck and upper limbs and abdomen groupsin groups 1 week after surgery (all p < 0.05). Various aspects of quality of life, including daily life, enjoyment of life, sleep, relationships, work, walking ability, and emotions, significantly decreased after surgery (p < 0.05). Especially in sleep duration, there was an increase in patients reporting intermediate sleep (4–7 h) and a proportion achieving a normal sleep duration of ≥7 h. And no significant differences of BPI were observed among different affected locations. The incidence of adverse events in the 0.5% doxorubicin group and 0.33% doxorubicin group was 8.78 and 6.34%, respectively. Conclusion CT-guided doxorubicin injection therapy has the potential to alleviate pain and enhance the quality of life in patients with PHN. Notably, the use of a 0.5% doxorubicin concentration yields more pronounced pain relief compared to a 0.33% concentration. While longer durations of PHN and specific affected sites may influence the response to treatment, the overall improvements in quality of life remain consistent.